Analisis Digital Marketing, Knowledge Sharing, E-WOM terhadap Niat Pembelian Layanan Program Bayi Tabung melalui Kepercayaan Konsumen - Purba, Kezia Christina Yeshua; Maradona, Agus Fredy (SAFE-Network, 2025)
In Vitro Fertilization (IVF) or test-tube babies is a form of ART that offers a solution for infertile couples. Trust in this program is very important, not only in medical personnel, but also in equipment and support services. This study aims to analyze the influence of digital marketing, knowledge sharing, and E-WOM on the intention to purchase IVF services through the mediating role of consumer trust. The data measurement technique used in the questionnaire to provide answers to each statement item is the 1-10 semantic differential scale. In this study, the data collection technique involves providing statements through Google Forms and disseminating them on social media. The data analysis technique used to draw conclusions from the study was the Structural Equation Model (SEM) approach using Smart PLS 3.2 software. This study found that digital marketing, knowledge sharing, and e-WOM have a positive and significant effect on consumer trust. Furthermore, digital marketing and e-WOM directly influence purchase intention in a positive and significant manner, while knowledge sharing does not significantly influence purchase intention directly. However, knowledge sharing can increase purchase intention through consumer trust. Consumer trust was also found to be a significant mediator in the relationship between digital marketing, knowledge sharing, and e-WOM with purchase intention.